Public versus Private Drug Insurance and Outcomes of Patients Requiring Biologic Therapies for Inflammatory Bowel Disease. (23rd January 2017) - Rumman, Amir; Candia, Roberto; Sam, Justina J.; Croitoru, Kenneth; Silverberg, Mark S.; Steinhart, A. Hillary; Nguyen, Geoffrey C.
Abstract : Background . Antitumor necrosis factor (anti-TNF) therapy is a highly effective but costly treatment for inflammatory bowel disease (IBD). Methods . We conducted a retrospective cohort study of IBD patients who were prescribed anti-TNF therapy (2007–2014) in Ontario. We assessed if the insurance type was a predictor of timely access to anti-TNF therapy and nonroutine health utilization (emergency department visits and hospitalizations). Results . There were 268 patients with IBD who were prescribed anti-TNF therapy. Public drug coverage was associated with longer median wait times to first dose than private one (56 versus 35 days, P = 0.002 ). After adjusting for confounders, publicly insured patients were less likely to receive timely access to anti-TNF therapy compared with those privately insured (adjusted hazard ratio, 0.66; 95% CI: 0.45–0.95). After adjustment for demographic and clinical characteristics, publicly funded subjects were more than 2-fold more likely to require hospitalization (incidence rate ratio [IRR], 2.30; 95% CI: 1.19–4.43) and ED visits (IRR 2.42; 95% CI: 1.44–4.08) related to IBD. Conclusions . IBD patients in Ontario with public drug coverage experienced greater delays in access to anti-TNF therapy than privately insured patients and have a higher rate of hospitalizations and ED visits related to IBD.